Coronavirus-19 phobia and health literacy in adults: A descriptive-correlational study - Emine Derya Ister; Filiz Taş (National Scientific Medical Center, 2022)
Aim: The aim of this study was to determine the levels of health literacy (HL) and COVID-19 Phobia (C19P-S) in adult individuals and was to evaluate the relationship between health literacy and coronavirus-19 phobia among adults. Materials and methods: The sample of this descriptive and correlational study consisted of 545 people living in Kahramanmaras city center and meeting the study criteria. Study data were collected through google forms using personal information form, Health Literacy Scale and Coronavirus-19 Phobia Scale (C19P-S). Results: The mean C19P-S score of the participants was 30±16.33. A statistically significant difference was determined between the mean C19P-S scores of women and men (p<0.05). It was determined that those with a middle income level, those who reported that they took adequate precautions to protect against coronavirus and those who did not receive health education had higher C19P-S score averages. According to the correlation analysis, there is no relationship between the health literacy total score and C19P-S [r(545)=-0.054; p>0.05]. There was a weak negative statistically significant correlation between the somatic sub-dimension of C19P-S and health literacy total score, access, understanding, and appraisal sub-dimensions (p<0.05). Conclusion: HL adult population was generally high and the coronavirus phobia was moderate. Addressing HL as a variable may be beneficial in the management of coronavirus phobia.